2022
DOI: 10.1177/21925682211073313
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial Quality Assessment in Adult Spinal Surgery: What Do Publication Status, Funding Source, and Result Reporting Tell Us?

Abstract: Study Design Narrative Review Objectives The objective of this study was to compare publication status of clinical trials in adult spine surgery registered on ClinicalTrials.gov by funding source as well as to identify other trends in clinical trials in adult spine surgery. Methods All prospective, comparative, therapeutic (intervention-based) trials of adult spinal disease that were registered on ClinicalTrials.gov with a start date of January 1, 2000 and completion date before December 17, 2018 were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
2
2
Order By: Relevance
“…Among these studies, 71% included fewer than 25 patients, 43–45,48,49 57% were characterized by a single‐arm, open‐label, and unblinded design, 44,45,48,49 with one study 45 having enrolled only 15% of the initially estimated population, therefore collectively providing a considerably low level of evidence. Previous investigations have shown that private‐ and industry‐funded trials in spine research were less likely to be published 12,50 . In our study, we did not find any statistical difference in terms of publication status among trials sponsored by universities and private companies.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Among these studies, 71% included fewer than 25 patients, 43–45,48,49 57% were characterized by a single‐arm, open‐label, and unblinded design, 44,45,48,49 with one study 45 having enrolled only 15% of the initially estimated population, therefore collectively providing a considerably low level of evidence. Previous investigations have shown that private‐ and industry‐funded trials in spine research were less likely to be published 12,50 . In our study, we did not find any statistical difference in terms of publication status among trials sponsored by universities and private companies.…”
Section: Discussioncontrasting
confidence: 67%
“…Previous investigations have shown that private-and industry-funded trials in spine research were less likely to be published. 12,50 In our study, we did not find any statistical difference in terms of publication status among trials sponsored by universities and private companies.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…will have to be answered through prospective, randomized control trials. Unfortunately, there is a dearth of high-quality clinical trials performed thus far in the United States; 7 however, work from your group as well as our other clinician/scientist colleagues in spine surgery will undoubtedly lead the way toward safely improving and optimizing patient outcomes.…”
mentioning
confidence: 99%